An interdisciplinary chronic pain rehabilitation program effectively treats impairment in sexual function, depression, alexithymia, and pain in women with chronic pelvic pain. (2nd October 2021) - Aboussouan, Alix B.; Mandell, Darcy; Johnson, Joseph; Thompson, Nicolas; Huffman, Kelly L.
Abstract: Purpose: Chronic pelvic pain (CPP) in women is often associated with marked emotional distress and disability, with particular impairments in sexual functioning. Research supports the efficacy of interdisciplinary chronic pain rehabilitation programs (ICPRPs) in treating chronic pain, however less is known about their utility in CPP. Methods: This retrospective study examined pain-related sexual impairment, emotional symptoms, and pain severity in CPP patients before and after completing a 3–4 week ICPRP. Predictors of post-treatment sexual impairment were also investigated. Participants included 58 female CPP patients and 58 age-matched females with non-pelvic chronic pain (NPCP). Results: All participants reported robust improvements across outcome measures. Women with CPP reported greater pre- and post-treatment impairment in sexual function than NPCP patients, despite significant treatment-related improvements. In contrast, CPP patients also reported higher levels of depression at baseline but showed greater treatment related-improvements. In participants with CPP, treatment-related improvements in depression, alexithymia, and pain severity significantly explained decreases in pain-related sexual impairment following treatment, whereas none of these variables explained sexual impairment outcomes in women with NPCP. Conclusion: Results demonstrate that ICPRPs can effectively treat CPP, particularly through changes in depression and alexithymia. Future research should examine whether specific interventions can be added in ICPRPS to address CPP-related sexual impairment.